DESIGN OF CLEAN WATER TRANSMISSION ON KIJANG â BINTAN BAY - Mubarak, Hifzil
One of the most important things to support activities on Kijang – Bintan Bay is the usage of clean water. One way to provide the need of clean water is through clean water production and transmission from the nearest source to the bay. The design process of clean water transmission starts with reviewing the variety of pipe materials and classes, followed by hydraulic and economic analysis to choose the right dimension of the pipe and the type of the pump. Each option of the transmission system will be analyzed based on the economic aspects so the most economical system will be chosen. The analysis is then followed by assessing pipe’s capability of withstanding internal and external pressure acting on its crown. From these results, the clean water transmission system will be obtained corresponding with the specifications and needs from the site. The results of this undergraduate thesis are components from production and transmission system, from the initial reservoir until the final reservoir of Pelindo, starting from pump head specification for each nominal diameter option, followed by comparing the investment and operational costs resulting in which nominal diameter that will be used in the system. The next result is the material class of the pipe, which is obtained by analyzing the stress in the pipe crown as the outcome of internal and external pressure acting on the pipe. The result of pump selection alongside the piping components combined with non-technical components is also reported in the investment and yearly cost of the clean water transmission system.